The collectivist and statist vocational training innovative institutions and self-employment earnings gaps - Pankaj Patel; Pejvak Oghazi (Journal of Innovation & Knowledge (JIK), 2024)
The entrepreneurship literature has long recognized the importance of education in fostering successful self-employment, yet a significant gap exists in our understanding of how the political economy of vocational education systems influences the financial success of self-employed graduates. We focus on vocational education systems that are collectivist - namely, collective decision making and stakeholder collaboration to align training with labor market needs and to promote social cohesion - and statist - a centrally controlled vocational education system directed by the state, aiming to align training with national development goals and to prioritize economic needs. Our study analyzed 6924 participants who received vocational education from collectivist systems (Czech Republic and Denmark) and statist systems (Finland and Norway). The findings show a significant earnings gap between employed and self-employed receiving vocational education in statist systems, and a non-significant difference in earnings between employed and self-employed in collectivist systems. The findings have implications for how the type of vocational training affects the earnings gaps among the employed and self-employed.
Keywords: J24; J32; L26; I25; I28; 650; Collectivist vocational education systems; Statist vocational education systems; Specific skills; Earnings gaps; Self-employed